Central Bank Digital Currency The Birth of the Digital Euro - Annunziata, Filippo; Hadjiemmanuil, Christos; Joosen, Bart (EBI Studies in Banking and Capital Markets Law, 2025)
XXIII, 333 p. 32 illus., 6 illus. in color.